The significant survival advantage of female sex in nasopharyngeal carcinoma: a propensity-matched analysis - OuYang, P-Y (Br J Cancer, 2015)
BACKGROUND: Whether females have better survival than males in nasopharyngeal carcinoma is barely acknowledged and the exact explanations remain unknown. METHODS: Overall, 5929 patients receiving treatment between January 2005 and December 2010 were separately stratified by stage into early and advanced stage groups, and by age into premenopausal (⩽45 years), menopausal (46–54 years) and postmenopausal (⩾55 years) groups. Matched males and females in each group were identified using the propensity score matching method. Differences in disease-free survival (DSS), overall survival (OS), distant metastasis-free survival (DMFS) and locoregional relapse-free survival (LRFS) were estimated by the Kaplan–Meier method and Cox regression model. RESULTS: Overall, 398, 923, 744, 319 and 313 pairs of males and females were matched in early stage, advanced stage, premenopausal, menopausal and postmenopausal group, respectively. Females showed significant advantage over males across all end points in both early and advanced stage groups (P⩽0.042). However, this advantage persisted at premenopausal age (P⩽0.042), declined during menopause (DMFS, P=0.021; DSS, P=0.100; OS, P=0.693; LRFS, P=0.330) and totally disappeared at postmenopausal age (P⩾0.344). CONCLUSIONS: Sex significantly affects NPC survival, with a definite female advantage regardless of tumour stage. Intrinsic biologic traits appear to be the exact explanation according to the declining magnitude of sex effect with age.